2010
DOI: 10.1163/000579510x511051
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of female preference for call source level in midwife toads Alytes cisternasii and A. obstetricans

Abstract: We address the question of whether female preference exerts selection on male calling energy (souce level). We investigate whether female midwife toads express a preference between advertisement calls that have different source levels but that reach them with similar intensities (due to differences in distance). Females were presented with pairs of recordings of identical synthetic calls, recorded at the same location in the field site, and reaching the microphone at similar sound levels (69 dB peak SPL). Stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Sexual selection has interested biologists for more than a century because it works differently to natural selection, leading to the evolution of sexual traits that are usually costly in fitness (darwin, 1871;Zahavi & Zahavi, 1997;Andersson & Simmons, 2006). Intra-sexual competition and mate choice have stimulated the majority of recent investigations (West-Eberhard, 1979;Hunt et al, 2009;Rafael et al, 2010, Liao & lu, 2011c. A majority of studies on sexual selection have shown that it usually results from a female choice for a particular sexual display, rarely from male mate choice.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual selection has interested biologists for more than a century because it works differently to natural selection, leading to the evolution of sexual traits that are usually costly in fitness (darwin, 1871;Zahavi & Zahavi, 1997;Andersson & Simmons, 2006). Intra-sexual competition and mate choice have stimulated the majority of recent investigations (West-Eberhard, 1979;Hunt et al, 2009;Rafael et al, 2010, Liao & lu, 2011c. A majority of studies on sexual selection have shown that it usually results from a female choice for a particular sexual display, rarely from male mate choice.…”
Section: Introductionmentioning
confidence: 99%